Circulating Microparticles in the Pathogenesis and Early Anticoagulation of Thrombosis in COVID-19 With Kidney Injury - Wang, Chengyue; Yu, Chengyuan; Novakovic, Valerie A.; Xie, Rujuan; Shi, Jialan (Frontiers in Cell and Developmental Biology, 2022)
As more is learned about the pathophysiological mechanisms of COVID-19, systemic thrombosis has been recognized as being associated with more severe clinical manifestations, mortality and sequelae. As many as 40% of patients admitted to the hospital due to COVID-19 have acute kidney injury, with coagulation abnormalities the main cause of impaired function. However, the mechanism of renal thrombosis and the process leading to kidney injury are unclear. Microparticles (MPs) are membrane bubbles released in response to activation, injury or apoptosis of cells. The phosphatidylserine (PS) exposed on the surface of MPs provides binding sites for endogenous and exogenous FXase complexes and prothrombin complexes, thus providing a platform for the coagulation cascade reaction and facilitating clot formation. In the context of COVID-19 infection, viral attack leads immune cells to release cytokines that damage circulating blood cells and vascular endothelial cells, resulting in increased MPs levels. Therefore, MPs can be used as a risk factor to predict renal microthrombosis and kidney injury. In this paper, we have summarized the latest data on the pathophysiological mechanism and treatment of renal thrombosis caused by MPs in COVID-19, revealing that the coagulation abnormality caused by MP and PS storms is a universal progression that aggravates the mortality and sequelae of COVID-19 and potentially other pandemic diseases. This paper also describes the risk factors affecting renal thrombosis in COVID-19 from the perspective of the Virchow’s triad: blood hypercoagulability, vascular endothelial injury, and decreased blood flow velocity. In summary, given the serious consequences of thrombosis, current guidelines and clinical studies suggest that early prophylactic anticoagulant therapy reduces mortality and improves clinical outcomes. Early anticoagulation, through inhibition of PS-mediated coagulopathy, allows maintenance of unobstructed blood circulation and oxygen delivery thereby facilitating the removal of inflammatory factors, viruses, MPs, and dead or damaged cells, and expediting patient rehabilitation.